2017
DOI: 10.1177/0890334417706359
|View full text |Cite
|
Sign up to set email alerts
|

Antibody Profile of Colostrum and the Effect of Processing in Human Milk Banks: Implications in Immunoregulatory Properties

Abstract: The supply of relevant immunological components is stable throughout the colostrum stage. The effects of pasteurization on antibodies depend on isotype, subclass, and specificity. This information is relevant to improving the immunological quality of colostrum, especially for preterm newborns.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
14
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 36 publications
2
14
0
1
Order By: Relevance
“…This study has shown the statistically significant advantage of HTST over HoP in relation to the preservation of these two Ig classes. Previous studies indicated that IgMs and IgGs are highly and moderate sensitive, respectively, to HoP ( 21 , 45 49 ). In contrast, IgG was highly resistant to any of the HTST treatment applied in this work, while inactivation of IgM depended on both processing parameters, temperature and time.…”
Section: Discussionmentioning
confidence: 98%
“…This study has shown the statistically significant advantage of HTST over HoP in relation to the preservation of these two Ig classes. Previous studies indicated that IgMs and IgGs are highly and moderate sensitive, respectively, to HoP ( 21 , 45 49 ). In contrast, IgG was highly resistant to any of the HTST treatment applied in this work, while inactivation of IgM depended on both processing parameters, temperature and time.…”
Section: Discussionmentioning
confidence: 98%
“…23,24 Natalizumab, an IgG 4 monoclonal antibody therapy for MS and inflammatory bowel disease, represents 1 notable exception because of more repeated dosing and the higher relative proportion of IgG 4 in mature breast milk than in serum. 25,26 Although low levels of natalizumab were reported in breast milk in 2 patients, 23 serial collection of breast milk over 50 days from infusion in another single patient suggested accumulation of natalizumab in breast milk. 27 By contrast, rituximab can be dosed once every 6–12 months and is an IgG 1 subclass with a large molecular weight (145 kD).…”
Section: Discussionmentioning
confidence: 99%
“…None of colostrum Ig levels were seen to present normal distributions. Using the results of the previous researches [23, 24], we determined that IgA is the main isotype in colostrum. This study reported that IgA2 (mean = 11.87 ± 2.904 mg/mL) concentration in the colostrum was slightly higher than IgA1 (mean = 9.893 ± 1.577 mg/mL).…”
Section: Resultsmentioning
confidence: 99%